Thyroid dysfunction in the wake of Omicron: understanding its role in COVID-19 severity and mortality - Zhang, Qingfeng; Zhang, Zongyue; Liu, Xu; Wang, Yixuan; Chen, Hao; Hao, Yueying; Zha, Shiqian; Zhang, Jingyi; He, Yang; Zhou, Beini; Hu, Ke (Frontiers in Endocrinology, 2024)
Purpose: SARS-CoV-2 can invade the thyroid gland. This study was to delineate the risk of thyroid dysfunction amidst the prevalence of the Omicron variant, and to investigate the correlation between thyroid function and Coronavirus disease 2019 (COVID-19) outcomes. The study also aimed to ascertain whether thyroid dysfunction persisted during COVID-19 recovery phase. Methods: This was a retrospective cohort study. COVID-19 patients from the Renmin Hospital of Wuhan University, China during the epidemic of Omicron variants were included, and their thyroid function were analyzed in groups. Results: A history of thyroid disease was not associated with COVID-19 outcomes. COVID-19 can lead to a bimodal distribution of thyroid dysfunction. The severity of COVID-19 was inversely proportional to the levels of thyroid- stimulating hormone (TSH), free triiodothyronine (FT3) and free thyroxine (FT4), leading to a higher prevalence of thyroid dysfunction. Severe COVID-19 was a risk factor for euthyroid sick syndrome (ESS) (OR=22.5, 95% CI, 12.1 - 45.6). Neutrophil to lymphocyte ratio mediated the association between severe COVID-19 and ESS (mediation effect ratio = 41.3%, p < 0.001). ESS and decreased indicators of thyroid function were associated with COVID-19 mortality, while high levels of FT3 and FT4 exhibited a protective effect against death. This effect was more significant in women (p < 0.05). During the recovery period, hyperthyroidism was quite uncommon, while a small percentage of individuals (7.7%) continued to exhibit hypothyroidism. Conclusion: COVID-19 severity was linked to thyroid dysfunction. Severe COVID-19 increased the risk of ESS, which was associated with COVID-19 mortality. Post-recovery, hyperthyroidism was rare, but some individuals continued to have hypothyroidism.